ANALISIS KESULITAN PENGUASAAN KONSEP TEORITIS DAN PRAKTIKUM KIMIA MAHASISWA CALON GURU KIMIA - yenni kurniawati (Konfigurasi : Jurnal Pendidikan Kimia dan Terapan, 2017)
Abstract The difficulties of preservice chemistry teacher in understanding theoretical and experimental chemistry were needed to be explored. This research was conducted to analyze students' difficulties in understanding theoretical and experimental chemistry courses, to obtained information that can be used as an evaluation for lecturers and faculty in an effort to improve the quality of preservice chemistry teacher. Mixed method with embedded design was used in this research by given priority to qualitative data as core and quantitative data to supported the analysis. This research found that teoretical inorganic and physical chemistry objects were the most difficult course for fifth semester students, whereas for the seventh graders physical and instrumental chemistry was the most difficult. The main causes of difficulty for students was the chemical abstractions plus the mathematic analysis that was not easily to deep understood by the students. Studets learning patterns and learning design are things that need to be improve to get better results. Kata Kunci: Kesulitan Mahasiswa, Kimia Teoritis, Praktikum Kimia